(untitled) (Researcher CAB: A Journal for Research and Development, 2024)
Mutual funds in Nepal are financial vehicles that pool money from multiple investors to invest in diversified portfolios of securities, managed by professional fund managers. They play a crucial role in mobilizing savings and providing access to diversified investment opportunities for Nepalese investors. This study examines the factors influencing investment decisions in mutual funds in Nepal, focusing particularly on financial literacy, risk perception, investment behavior, and peer group influence. To achieve the stated objective, data were collected from the primary source using a structured questionnaire administered through convenience sampling technique. The respondents comprised 204 individual investors of mutual funds inside the Kathmandu Valley. The Smart PLS 4.0 was used to analyze the structural relationships within the proposed theoretical model. The findings of this study validated the set hypotheses that financial literacy, risk perception and investment behaviour have positive and significant effect on investment decisions among the investors in Nepalese mutual funds but the peer group has no any effect on investment decision. These results underscore the importance of targeted financial education programs and tailored investment strategies that enhance individual investor knowledge and understanding, thereby fostering more informed and independent investment decisions in Nepal’s mutual fund market. The results may encourage to promote financial literacy through educational programs and integrating it into national curricula can empower investors to make informed decisions in Nepalese context.